Concordance of chlamydia infections of the rectum and urethra in same-sex male partnerships: a cross-sectional analysis. Issue 1 (December 2017) - Cornelisse, Vincent; Sherman, Christopher; Hocking, Jane; Williams, Henrietta; Zhang, Lei; Chen, Marcus; Bradshaw, Catriona; Bellhouse, Clare; Fairley, Christopher; Chow, Eric
Abstract Background Our study aimed to describe the concordance of chlamydia infections of the rectum and urethra in men who have sex with men (MSM) and their male partners. Methods This was a cross-sectional study of chlamydia in MSM and their male sexual partners both attending Melbourne Sexual Health Centre (MSHC), Australia, between February 2011 and March 2015. We excluded partnerships where testing for chlamydia at both the rectum and urethra were not undertaken. Results Our study included 473 partnerships (946 men). 30 men had urethral chlamydia, of whom 14 (47%, 95% CI 28 to 66) had a partner with rectal chlamydia. 46 men had rectal chlamydia, of whom 14 (30%, 95% CI 18 to 46) had a partner with urethral chlamydia. The proportion of men with rectal chlamydia when their partner had urethral chlamydia was significantly higher than the proportion of men with urethral chlamydia when their partner had rectal chlamydia (McNemar's p = 0.02). Conclusions This is the first study of chlamydia concordance in male sexual partnerships and suggests that transmission of chlamydia between the urethra and rectum may be less efficient than has been reported for transmission between the urethra and cervix in heterosexual couples. It also suggests that transmission from the urethra to the rectum may be more efficient than in the opposite direction.